Effects of high temperature melting on fractionation of heavy metals in sewage sludge - Idris, Azni; Saed, Katayon (Informa UK Limited, 2002)
Sewage sludge from aerobic treatment plant was found to contain high amounts of heavy metals. Research was carried out to investigate the speciation and leaching behavior of heavy metals when using high temperature melting technology for treatment. This was achieved by conducting a sequential chemical extraction procedure and EP-TOX leaching test. The thermal treatment led to increased shift of metals from organic fraction to residual fraction, indicating that the thermal treatment caused metals in sewage sludge to become stable. Furthermore, results from leaching test revealed that metals were not leached from the final product after thermal treatment and this was verified using US EPA standard limits. Results from this study indicated that melting technology could convert the sludge to product that can be either reused or landfilled without an adverse environmental impact.